Management of oral cavity bleeding in haemophilia patients: Tatalaksana perdarahan rongga mulut pada pasien hemofilia - Nilawati Sakka; Andi Tajrin; Mukhtar Nur Anam (Makassar Dental Journal PDGI Makassar, 2023)
Haemostasis disorders are classified as coagulation factor deficiency, platelet disorders, vascular disorders and fibrinolytic de-fects. Haemophilia belongs to the first group of these diseases which are inherited recessively linked to the X-chromosome. Haemophilia is clinically characterised by serious and prolonged bleeding. Bleeding of the oral mucosa is often an incidental finding in children with haemophilia. A 1-year-old boy with complaints of persistent bleeding of the gums due to trauma by impact of a plastic water bottle since ±9 days was reported. The management of the case was routine blood tests, PT, aPTT and coagulation factor concentrations, debridement and hecting vulnus under general anaesthesia, joint care with the paedia-tric department of the HOM division, and administration of factor VIII injection. It was concluded that haemophilia is a seri-ous congenital bleeding disorder that requires early diagnosis. Anamnesis, clinical examination, supporting examination, and management must be prompt and appropriate to prevent further complications.